Application of Teaching Materials for Introduction to Elementary Level Numbers and Letters for Elementary School Teachers in Maros Regency: Penerapan Bahan Ajar Untuk Pengenalan Angka dan Huruf Tingkat Dasar Bagi Guru-guru SD di Kabupaten Maros - Rusdianto Rusdi; S. Sapinah; Isma Muthahharah; Hariani Harjuna; S. Sugianty (Yayasan Ahmar Cendekia Indonesia, 2022)
The solutions offered in this service activity are 1) to motivate students to be interested in learning the basic material, namely numbers and letters, 2) to increase teacher knowledge in determining the type of teaching materials that are suitable to be applied, 3) To motivate teachers to improve their skills. can make children interested in the material presented. The service activity was carried out at SMP Negeri 14 Tanralili, Maros Regency by involving elementary school teachers who were around the school. The results of this service activity are 1) showing the enthusiasm of the teachers to respond to the application of teaching materials for the introduction of basic letters and numbers, this is indicated by the presence of teachers who ask questions, suggestions and criticisms, 2) There is an increase in teachers' knowledge and understanding of the concept of recognizing numbers and letters for elementary school teachers, 3) There is a positive response from the participants which is marked by working on independent assignments.